2010
DOI: 10.1590/s0103-507x2010000400003
|View full text |Cite
|
Sign up to set email alerts
|

Nível plasmático de homocisteína: marcador de gravidade em pacientes sépticos?

Abstract: Objective: Homocysteine and sepsis are both associated with inflammation and endothelial activation. Therefore this study was aimed to evaluate if the plasma homocystein level is related with the septic patient clinical severity. Methods: Severe sepsis or septic shock patients, with less than 48 hours from organ dysfunction start, were admitted to this prospective observational study. Homocysteine levels were determined by the time of study admission and then on the Days 3, 7 and 14. The homocysteine associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…4. Basal homocysteine levels have been found to not be associated with the severity and mortality of septic patients [15]. In a study by Tsantes et al [16], basal homocysteine levels in sepsis patients were observed to be within normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…4. Basal homocysteine levels have been found to not be associated with the severity and mortality of septic patients [15]. In a study by Tsantes et al [16], basal homocysteine levels in sepsis patients were observed to be within normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…1 . Finally, 16 cohort studies 17 18 19 20 21 22 23 24 25 26 34 35 36 37 38 39 were available for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1 , 16 cohort studies were included in the meta-analysis. Six of them were prospective cohort studies 17 19 21 34 36 39 and the remaining were retrospective cohort studies 18 20 22 23 24 25 26 35 37 38 . These studies were performed in Austria 17 18 20 , Greece 21 , Brazil 19 , the United States 35 36 , Iran 34 , and China 22 23 24 25 26 37 38 39 , and all included critically ill patients who were admitted to the ICU, such as patients with sepsis, pulmonary embolism, acute myocardial infarction, severe acute pancreatitis, respiratory failure, intracerebral hemorrhage, and severe multiple trauma etc.. Serum Hcy was measured within 48 hours of ICU admission, and the follow-up durations varied from 2 weeks to 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations